The Routledge handbook of self-determination and secession
1 online resource.
Keywords: "The Routledge Handbook of Self-Determination and Secession explores the various debates surrounding the issues of self-determination and secession, and the legal, political, and normative implications they give rise to. Offering a broad survey of the state of the sub-discipline today, the chapters are divided into seven key parts: an Introduction, Self-Determination, Explaining and Justifying Secession, Secession Strategies, Counter-Secession Strategies, International Law and Secession, and Constitutional Law and Secession. The authors, from a range of disciplinary backgrounds, explore all the recent approaches to secession and self-determination based on strategic interaction of major actors in a secession process. This handbook will be of great interest to students and researchers from a variety of disciplines including politics and international relations, security studies, and law"--